Where Things Go - Aubert, Baptiste (Journal of Anthropological Films, 2023)
In the mid-60s, in the small Belgian town of Verviers, most of the textile factories that had contributed to the town’s prosperity closed down. On witnessing the end of an epoch, the town council decided to put together a collection of old textile machines that is now stored in an old industrial shed. The film portrays a group of retired men spending their free time repairing the machines and creating a Lieu de mémoire where they relive their former professional activity. Imitating their passion, I created my own collection of former industrial objects. By buying old weaving shuttles from flea market sellers that wanted to get rid of them, I sought to give a sense of the fragile collective memory of the city inhabitants where memories compete with oblivion. Like the warp and weft of a fabric, these two filmic materials weave together to form the film Where Things Go—a film that questions the attachment we have to things, to memory, and to the past.